Implementasi Program KKN dalam Pemberdayaan Masyarakat di Desa Pematang Cengkering Melalui Bidang Pendidikan, Ekonomi, dan Pertanian - Inggit Aprilia Utami; Lisa Septia Dewi Br.Ginting; Latifa Ramadhani; Luthfiah Alvina Zahra Harahap; Susilawati Berutu (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Community Service Program (KKN) is a form of student engagement to integrate knowledge and skills for village empowerment. KKN Group 26 from Universitas Muslim Nusantara Al-Washliyah was conducted in Pematang Cengkering Village, Medang Deras Subdistrict, Batu Bara Regency, from July 14 to August 2, 2025. The program aimed to improve community quality of life through education, economy, and agriculture. The implementation method employed a participatory approach, involving college students, village officials, and community members. The programs included literacy tutoring Reading, Writing, and Arithmetic (calistung) for children, training on snack production, packaging, and marketing strategies for (UMKM), as well as the cultivation of Family Medicinal Plants (TOGA) as an effort to promote natural health self-sufficiency. The results showed increased interest in basic literacy among children, improved creative economic skills for housewives, and community awareness of TOGA utilization. In conclusion, the KKN program in Pematang Cengkering Village has made a positive contribution to community empowerment by strengthening educational capacity, supporting local economic growth, and fostering sustainable agricultural innovation.